PENERAPAN PENGGUNAAN MEDIA PEMBELAJARAN SMART BOX UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPAS DI SD NEGERI TANABANGKA KABUPATEN GOWA - Syamsuryani Eka Putri Atjo; Siti Raihan; Asri Nurfadilah Aulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is the low learning outcomes grade V students in the subject of science at SD Negeri Tanabangka, Gowa Regency. This study aims to describe the application of the use of smart box learning media in improving the learning outcomes of grade V students in the subject of science at SD Negeri Tanabangka, Gowa Regency. The approach used in this study is a qualitative approach. The type of research used is Classroom Action Research (CAR). This study was conducted in two cycles, each consisting of two meetings with activity stages including, planning, implementation, observation and reflection. The focus of the research in this study is the application of Smart Box learning media and student learning outcomes. The research subjects were teachers and all grade V students in the subject of science at SD Negeri Tanabangka, Gowa Regency. totaling 35 students consisting of 16 boys and 19 girls. Data collection techniques were carried out through observation and tests. The research instruments used were teacher and student observation sheets, as well as student learning outcome assessment sheets. The data analysis techniques used were qualitative and quantitative data analysis techniques. The results of the study on the application of Smart Box learning media to improve the learning outcomes of grade V students in the subject of science at SD Negeri Tanabangka, Gowa Regency. in the implementation of the first cycle were in the sufficient category, and there was an increase in the second cycle which was in the good category and achieved the predetermined indicators, namely the results of teacher and student observations obtained a percentage value of ≥ 76%. The conclusion of this study is that by implementing Smart Box learning media, it can improve the learning outcomes of grade V students in the subject of science at SD Negeri Tanabangka, Gowa Regency.